2003
DOI: 10.1016/s0735-1097(03)00159-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluid retention after initiation of thiazolidinedione therapy in diabetic patients with established chronic heart failure

Abstract: Although fluid retention after treatment with TZD in diabetic patients with chronic systolic HF occurs, the mechanism is undefined. Fluid retention related to TZD tends to be peripheral and is usually reversible after drug withdrawal. No direct association between the risk of fluid retention and the baseline degree of severity of HF was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2
6

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 16 publications
2
71
2
6
Order By: Relevance
“…Therefore, the effect on LV pressure may be caused in part by pioglitazone-induced fluid retention [20]. Despite increased vascular density at the peri-MI by pioglitazone administration, % fibrosis volume was not changed; therefore, this angiogenic effect could not help reduce % fibrosis volume, in the present study.…”
Section: The Effect Of Orally Administrated Pioglitazone In Cardiac Fcontrasting
confidence: 52%
See 1 more Smart Citation
“…Therefore, the effect on LV pressure may be caused in part by pioglitazone-induced fluid retention [20]. Despite increased vascular density at the peri-MI by pioglitazone administration, % fibrosis volume was not changed; therefore, this angiogenic effect could not help reduce % fibrosis volume, in the present study.…”
Section: The Effect Of Orally Administrated Pioglitazone In Cardiac Fcontrasting
confidence: 52%
“…4B). Orally administrated pioglitazone alone improved LV systolic pressure of CNT groups, whereas it did not improve echocardiographic parameters, suggesting that pioglitazone-induced water retention [20] might have played a role in this LV pressure to some extent.…”
Section: Effect Of Ppar-c-activated Bm-msc Transplantation On Cardiacmentioning
confidence: 83%
“…Indeed, several investigators have reported that thiazolidinediones (TZD), such as pioglitazone, potentially induced the appearance of edema and subsequent CHF in diabetic patients [26,27]. In contrast, Tang et al have most recently shown the lack of direct association between the risk of fluid retention and the baseline degree of severity of CHF by the treatment with TZD in diabetic patients [28]. Therefore, although the precise mechanism(s) is not clear, it is likely that the reduction of the insulin amount by some insulin-sensitizing agents may, at least, be efficient for the decrease of plasma BNP level, since insulin has the potential to induce sodium retention and volume expansion.…”
Section: Discussionmentioning
confidence: 99%
“…A higher risk of heart failure has been reported in some studies (25), whereas others have actually suggested a reduced risk of heart failure in glitazone-treated patients (26). A recent analysis demonstrated reduced mortality in patients with a prior history of heart failure who were treated with glitazones (27).…”
Section: Glitazones: Other Considerationsmentioning
confidence: 98%